The Effect of Increasing Donor Age on Myocardial Ischemic Tolerance in a Rodent Model of Donation After Circulatory Death. Issue 6 (18th May 2021) - Villanueva, Jeanette E.; Chew, Hong C.; Gao, Ling; Doyle, Aoife; Scheuer, Sarah E.; Hicks, Mark; Jabbour, Andrew; Dhital, Kumud K.; Macdonald, Peter S.
Abstract : Background: Hearts from older donors or procured via donation after circulatory death (DCD) can alleviate transplant waitlist; however, these hearts are particularly vulnerable to injury caused by warm ischemic times (WITs) inherent to DCD. This study investigates how the combination of increasing donor age and pharmacologic supplementation affects the ischemic tolerance and functional recovery of DCD hearts and how age impacts cardiac mitochondrial respiratory capacity and oxidative phosphorylation. Methods: Wistar rats (12-, 18-, and 24-mo-old) were subjected to DCD with 20-min fixed WIT. Hearts were procured, instrumented onto a Langendorff perfusion circuit, flushed with Celsior preservation solution with or without supplementation (glyceryl trinitrate [GTN]/erythropoietin [EPO]/zoniporide [Z]) and perfused (Krebs-Henseleit buffer, 37°C Langendorff 30-min, working 30-min). Cardiac functional recovery of aortic flow (AF), coronary flow (CF), cardiac output (CO), and lactate dehydrogenase release were measured. Native heart tissue (3-, 12-, and 24-mo) were assessed for mitochondrial respiratory capacity. Results: Unsupplemented 18- and 24-month DCD hearts showed a 6-fold decrease in AF recovery relative to unsupplemented 12-month DCD hearts. GTN/EPO/Z supplementation significantly increased AF and CO recovery of 18-month DCD hearts to levels comparable to supplemented 12-month hearts; however, GTN/EPO/Z did not improve 24-month DCD heart recovery. Compared to 12-month heart tissue, 24-month hearts exhibited significantly impaired mitochondrial oxygen flux at complex I, II, and uncoupled maximal respiration stage. Conclusions: Reduced ischemic tolerance after DCD was associated with increasing age. Pharmacologic supplementation improves functional recovery of rat DCD hearts but only up to age 18 months, possibly attributed to a decline in mitochondrial respiratory capacity with increasing age.